Heterogeneity in Needs and Negative Marginal Tax Rates - Spencer Bastani; Sören Blomquist; Luca Micheletto (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper highlights the possibility that negative marginal tax rates arise in an intensive-margin optimal income tax model where wages are exogenous and preferences are homogeneous, but where agents differ both in skills (labor market productivity) and their needs for a work-related consumption good.
Keywords: H21; 330; nonlinear income taxation; negative marginal tax rates; heterogeneity in needs; redistribution